Preprocedural ECG‐Gated Computed Tomography for Prevention of Complications during Lead Extraction. Issue 10 (8th September 2014) - LEWIS, ROBERT K.; POKORNEY, SEAN D.; GREENFIELD, RUTH ANN; HRANITZKY, PATRICK M.; HEGLAND, DONALD D.; SCHRODER, JACOB N.; LIN, SHU S.; MILANO, CARMELO; DAUBERT, JAMES P.; SMITH, PETER K.; HURWITZ, LYNNE M.; PICCINI, JONATHAN P.
<x xml:space="preserve">Abstract</x> Background Preprocedural multidetector computed tomography (MDCT) may identify patients at risk for mechanical complications during lead extraction. Methods To describe the use and feasibility of computed tomography scanning for preprocedural planning of lead extraction, we conducted a retrospective study of high‐risk patients, who underwent electrocardiogram (ECG)‐gated MDCT before planned lead extraction between January 1, 2012, and March 30, 2013. Results Among 30 patients the mean age was 63 ± 15 years, 60% were male, and 20% had prior sternotomy. Most devices were left sided (93%) and 24 had implantable defibrillators (80%). Indications for extraction included lead malfunction (n = 15; 50%), class I lead advisories (n = 11; 37%), and infection (n = 10; 33%). Overall, there were 65 leads extracted (mean 2.1 leads per patient). One extraction procedure was deferred due to MDCT evidence of significant myocardial perforation with the lead tip > 1 cm beyond the epicardium (n = 1, 3%). MDCT suggestion of lead adherence to central venous structures (n = 13, 43%) was associated with significantly longer laser times (88 ± 71 seconds vs 30 ± 37 seconds, P = 0.02) and larger sheath size (14.9 ± 1.3 vs 13.5 ± 1.2 French, P = 0.02). MDCT evidence of central venous occlusion or stenosis was not associated with increased laser times. Excluding the patient with MDCT evidence of significant perforation, clinical success was achieved in all patients (n = 29/29). Conclusions ECG‐gated MDCT scanning before lead extraction may facilitate the identification of significant perforation and patients at high risk for mechanical complication.